Systematic Review of the Builder Method and Product of the Information System Strategic Planning at Higher Education Institution in Indonesian - Bernadus, Gunawan Sudarsono; Aedah, Abd Rahman; Sri, Poedji Lestari; Alexius, Ulan Bani (2020)
Research on the utilization of Information System Strategic Planning (ISSP) in Higher Educations in Indonesia is still being conducted. ISSP provides an important role in the successful use of information systems in Higher Education in the form of the realization of benefits. Therefore ISSP needs to be built properly by utilizing the appropriate ISSP builder methods, to produce ISSP products that can provide benefits realization. Current ISSP building methodologies commonly used are frameworks such as Business Systems Planning (BSP), Ward and Peppard (W&P), Zachman Enterprise Architecture (EA), Enterprise Architecture Planning (EAP), EA TOGAF (The Open Group Architecture Framework), Tozer, PPDIOO (Prepare, Plan, Design, Implementation, Operate, Optimize) and EUP (Enterprise Unified Process). Commonly produced ISSP products are Blueprint(BLPT), Application Portfolio(APPF), EA Model(EAMD), Strategic Planning (STPN), Master Plan(MTPN), and Road Map (RDMP). The results of research that discuss building methodologies and ISSP products are currently being conducted at Higher Education in Indonesia, but there is still little research that discusses the exploration of the accumulated use of the ISSP method, ISSP products, and mapping of ISSP methodologies to ISSP products. This exploration effort is useful in obtaining reality and phenomena related to ISSP product development methodologies and their mapping. The research aims to explore the method of ISSP builders and products and their mapping at Higher Educations in Indonesia in the period 2009 to 2019 by utilizing the Systematic Literature Review (SLR) method. The results of this study provide synthesis and mapping related to the ISSP builder method and products in Indonesia.